Prognostic Significance of PD-L1 Expression and Standardized Uptake Values in the Primary Lesions of Stage IV Adenocarcinoma Lung Cancer - Tien Cong, Bui; Cam Phuong, Pham; Thai, Pham-Van; Thuong, Vu-Le; Quang Hung, Nguyen; Hang, Dong-Thi; Anh Tuan, Hoang; Minh Khuy, Doan; Tuyen, Pham-Van; Minh Duc, Nguyen (Frontiers in Medicine, 2022)
Background: This study evaluated the prognostic ability of 18F-fluorodeoxyglucose (18F-FDG) positron emission tomography (PET)/computed tomography (CT) in patients with stage IV adenocarcinoma lung cancer to detect protein death-ligand 1 (PD-L1) expression levels Methods: In total, 86 patients with stage IV adenocarcinoma lung cancer underwent 18F-FDG PET/CT imaging and PD-L1 expression evaluation before treatment from February 2019 to November 2020 at Bach Mai Hospital, Hanoi, Vietnam. The assessed patient characteristics in this study included sex, age, smoking status, epidermal growth factor receptor (EGFR) mutation, PD-L1 expression level, survival status, tumor, node, and metastasis (TNM) stage, and metastasis locations. Results: The average age was 62.23 ± 9.51 years, and men and women represented 67.4% and 32.6% of the population, respectively. The EGFR mutation rate was 36%. PD-L1 expression was negative (detected in <1% of the tumor) in 40.7% of cases and positive in 59.3% of cases (detected in 1%–49% of the tumor in 32.6%; detected in ≥50% of the tumor in 26.7%). The mean maximum standardized uptake value (SUVmax) was 11.09 ± 3.94. SUVmax was significantly higher in PD-L1–positive tumors than in PD-L1–negative tumors (12.24 ± 4.01 and 9.43 ± 3.22, respectively; p = 0.001). Receiver operating characteristic curve analysis revealed an area under the curve of SUVmax was 0.681 (95% confidence interval 0.570–0.793, p = 0.004). Compared with PD-L1–negative cases, SUVmax was significantly different in all PD-L1–positive cases (p = 0.001), weakly PD-L1–positive cases (1%-49%, p = 0.005), and strongly PD-L1–positive cases (≥50%, p = 0.003). PD-L1 expression levels were significantly associated with SUVmax (p = 0.001), tumor size (p = 0.022), and EGFR mutation status (p = 0.045). Conclusions: SUVmax in the primary lesions was able to predict PD-L1 expression and may play a role in predicting PD-L1 immunotherapy efficacy in patients with stage IV lung adenocarcinoma.